The clinical development of antibody-drug conjugates for non-small cell lung cancer therapy - Liu, Xinlin; Deng, Junwen; Zhang, Renshuai; Xing, Jiyao; Wu, Yudong; Chen, Wujun; Liang, Bing; Xing, Dongming; Xu, Jiazhen; Zhang, Miao (Frontiers in Immunology, 2023)
Despite the emergence of molecular targeted therapy and immune checkpoint inhibitors as standard first-line treatments for non-small cell lung cancer (NSCLC), their efficacy in some patients is limited by intrinsic and acquired resistance. Antibody-drug conjugates (ADCs), a revolutionary class of antitumor drugs, have displayed promising clinical outcomes in cancer treatment. In 2022, trastuzumab deruxtecan (Enhertu) was approved for treating HER2-mutated NSCLC, thereby underscoring the clinical value of ADCs in NSCLC treatment strategies. An increasing number of ADCs, focusing on NSCLC, are undergoing clinical trials, potentially positioning them as future treatment options. In this review, we encapsulate recent advancements in the clinical research of novel ADCs for treating NSCLC. Subsequently, we discuss the mechanisms of action, clinical efficacy, and associated limitations of these ADCs.